[Letter] Lokoja [to] Mr. Baylis - Alvarez, Thos. E. (Adam Matthew Digital, 1908)
Ms. letter from Thomas E. Alvarez to Mr. Baylis discussing administrative matters of the Lokoja mission, including the work of Dr. Miller and himself, two probationary women missionaries, and building repairs to the Rev. Low's house